Mussolini’s dream factory: film stardom in fascist Italy - Gundle, Stephen (Berghahn Books, 2013)
The intersection between film stardom and politics is an understudied phenomenon of Fascist Italy, despite the fact that the Mussolini regime deemed stardom important enough to warrant sustained attention and interference. Focused on the period from the start of sound cinema to the final end of Fascism in 1945, this book examines the development of an Italian star system and evaluates its place in film production and distribution. The performances and careers of several major stars, including Isa Miranda, Vittorio De Sica, Amedeo Nazzari, and Alida Valli, are closely analyzed in terms of their relationships to the political sphere and broader commercial culture, with consideration of their fates in the aftermath of Fascism. A final chapter explores the place of the stars in popular memory and representations of the Fascist film world in postwar cinema.